Soil Degradation Studies Under Different Land Use System in an Arid Environment - Raina, Pramila; Sen, A K (Annals of Arid Zone, 2016)
Local (micro level) soil degradation processes going on in Jhanwar and Doli villages of Jodhpur district in different land use systems have been studied.The cultivation.on marginal land accelerate the wind erosion and the use of poor quality irrigation water is creating sodicity problem in soil resulting in severe degradation. Pasture land ha